The Role of Contemporary Islamic Education Teachers: Learning Evaluation as a Path Toward Public Trust in the 21st Century. - Al-Hakim, Dzaky Nabil; Wijayanti, Fitriana Wahyu; Wicaksana, Alfian Satria; Annur, Fauzi (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2025)
This study aims to comprehensively analyze the competencies of Islamic Religious Education (PAI) teachers in addressing the challenges of the 21st century, focusing on the role of learning evaluation as a means to build public trust in Islamic education. The research employs a library research method with a content analysis approach, reviewing recent scholarly works related to 21st-century teacher competencies, authentic assessment, and the Merdeka Curriculum. The findings reveal that 21st-century PAI teachers must possess holistic competencies encompassing pedagogical, professional, social, and personal dimensions strengthened by emotional intelligence (EQ) and spiritual intelligence (SI). Teachers are not merely knowledge transmitters but facilitators of values, moral mentors, and reflective evaluators who assess both learning processes and outcomes comprehensively. Learning assessment in PAI should be authentic, contextual, and technology-based, evaluating the balance between cognitive, affective, and psychomotor aspects. Honest and transparent evaluation practices foster accountability and enhance public trust in Islamic educational institutions. The study highlights the necessity for a paradigm shift in Islamic education—from a knowledge-transfer model toward a value-based character formation approach. Consequently, 21st-century PAI teachers are expected to serve as transformative agents capable of integrating professionalism, digital literacy, and spirituality within an adaptive and meaningful educational practice.